1984
DOI: 10.1115/1.3246657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Location in an Array on Heat Transfer to a Short Cylinder in Crossflow

Abstract: An experiment was conducted to measure the heat transfer from a heated cylinder, three diameters in length, in crossflow in an array of identical circular cylinders. Both in-line and staggered array patterns were studied. The cylinders were spaced on a 2.67 × 2.67 pitch. The Reynolds number range, based on cylinder diameter and average unobstructed channel velocity, was from 5000 to 125,000. Turbulence intensity profiles were measured for each case at a point one-half space upstream of the row containing the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 0 publications
3
31
0
Order By: Relevance
“…The only exception found is Simoneau and VanFossen [1984], who studied the pin fin heat transfer on a single row of It is also most common in the literature to focus heat transfer measurements directly within the pin fin array and not on the endwall upstream and downstream of the pin fins. Although the measurements were confined to a narrow strip 0.5 pin diameters long in the streamwise direction, Uzol and Camci [2005] studied the endwall heat transfer downstream of pin fin arrays.…”
Section: Uniqueness Of Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The only exception found is Simoneau and VanFossen [1984], who studied the pin fin heat transfer on a single row of It is also most common in the literature to focus heat transfer measurements directly within the pin fin array and not on the endwall upstream and downstream of the pin fins. Although the measurements were confined to a narrow strip 0.5 pin diameters long in the streamwise direction, Uzol and Camci [2005] studied the endwall heat transfer downstream of pin fin arrays.…”
Section: Uniqueness Of Researchmentioning
confidence: 99%
“…Using the Reynolds number definition mentioned above, Simoneau and VanFossen [1984] reported that the pin heat transfer on the single pin was only 7 to 15% lower than the pin heat transfer of the row with S/d = 2.67 pin spacing. However, the velocity ratio between the two cases was 1.55.…”
Section: Pin Spacing Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). The addition of one or more rows of pins in an inline pattern upstream of the measuring pin increased the heat transfer by about 50 percent, independent of the number of upstream rows.…”
Section: Introductionmentioning
confidence: 99%
“…Matsumoto et al [19] studied the end wall heat transfer in the presence of inline and staggered adiabatic circular pin fins. A review of staggered array pin fin heat transfer for turbine cooling applications was presented by Armstrong and Winstanley [20]. Bayram Sahin, Alparslan Demir [2] studied the heat transfer enhancement and pressure drop over a flat surface equipped with square crosssectional and modification as perforated pin fins in a rectangular channel.…”
Section: Literature Surveymentioning
confidence: 99%